The impact of economic factors on the relationships between psychological contract breach and work outcomes: a meta-analysis. Issue 3 (20th October 2020) - Jayaweera, Thushel; Bal, Matthijs; Chudzikowski, Katharina; de Jong, Simon
Abstract : Purpose: The purpose of this paper is to explore the macroeconomic factors that may moderate the psychological contract breach (PCB) and work outcome relationship. Design/methodology/approach: This study conducted a meta-analysis based on data from 134 studies. Findings: The study revealed that the inflation rate and the unemployment rate of a country moderated the association among employee PCB, job performance and turnover. Research limitations/implications: The availability of more detailed macroeconomic data against the PCB and outcome relationship for other countries and studies examining the impact of micro-economic data for PCB and outcome relationship would provide a better understanding of the context. Practical implications: The authors believe that the results highlight the importance of the national economy since it impacts individual outcomes following a breach. Social implications: Employment policies to capture the impact of macroeconomic circumstances as discussed. Originality/value: One of the valuable contributions made by this paper is that the authors capture the current accumulative knowledge regarding the breach and performance and breach and turnover relationship. Second, the study examines how the inflation rate and unemployment rate could moderate the association between PCB and job performance and turnover.